The consequences of digital revolution in monetary realm - Lukić Velimir; Živković Aleksandar (Anali Ekonomskog fakulteta u Subotici, 2018)
The digital revolution touches upon every aspect of our life, and accordingly has not circumvented the monetary realm. Three attributes of modern money are still tied to the power of state. First, the state prescribes what should be used as legal tender within its borders. Second, the state keeps for itself the exclusive right of issuing money. Thirdly, it is imposed as the sole regulator of money circulation in the country. Digitization threatens to shatter these postulates of contemporary monetary system. The first decade of XXI century was marked by the electronic money and the second is characterized by digital currency. This paper deals with the repercussions of new technologies on the monetary system, compares the characteristics of official and digital currency, explains the blockchain technology that lies at the heart of all digital currencies and shows its potential applications in other areas. The paper concludes that digital currencies do not possess all that is necessary to take over the primacy role from the national currencies. However, digitized reality is reflected in the digital currency, which raises broader social cognitive changes with regard to the phenomenon of money.